Human Resource Management and Staff Productivity in Colleges of Education in North Central, Nigeria - ABISOYE, Fausat Motunrayo; AJAGBE, Seun Weyinmi. (International Journal of Educational Management, 2025)
productivity in Nigerian Colleges of Education in North Central. This study adopted the descriptive survey research design. The population of the study comprised of all the 13 public Colleges of Education in the North Central, Nigeria. All the non academic staff of these institutions served as total population of the respondents. The study made use of purposive sampling technique to select seven (7) Colleges of Education. That is, three (3) Federal Colleges of Education and four (4) State Colleges of Education. Proportional sampling technique was use to select 10 percent non-academic staff each from the seven selected Colleges of Education making three hundred and thirty eight (338) sampled respondents. Data collected through self designed questionnaire titled ’Human Resource Management and Staff Productivity Questionnaire (HRMSPQ) was analyzed using T test, Pearson Product Moment Correlation and Multiple Regression. All the hypotheses were tested at 0.05 level of significance. The results from the analysis revealed that there was significant difference in the productivity of male and female staff. Staff training (r = 0.200, p<0.05) and staff promotion (r = 0.221, p<0.05) also had significant relationship with staff productivity. The study concluded that both staff training and staff promotion could jointly influence staff productivity with a great extent. The study recommended that the College Management should ensure constant job orientation training for staff and improve the promotion criteria and the benefits that staff receives on promotion.